Deoxyribonucleic acid amplification and hybridisation in Crohn's disease using a chlamydial plasmid probe. Issue 9 (September 1991) - McGarity, B H; Robertson, D A; Clarke, I N; Wright, R
Abstract : The possibility that Crohn's disease is caused by infection with Chlamydia trachomatis was examined by probing for chlamydial plasmid deoxyribonucleic acid (DNA) in DNA extracts from Crohn's disease tissue and by means of a serological study. Gut DNA extracts were obtained from 10 patients with Crohn's disease and four control subjects and were probed with a chlamydial plasmid probe after Southern blotting. The polymerase chain reaction was also used to amplify any chlamydial plasmid DNA present in tissue DNA extracts, before Southern blotting and probing. Chlamydial proctitis control specimens were not available: gut DNA extracts mixed with traces of chlamydia plasmid served as positive controls. Using these techniques, no chlamydial plasmid DNA sequences were found in Crohn's disease tissue. An enzyme linked immunosorbent assay for C trachomatis LI was performed on 48 patients with Crohn's disease and 48 control subjects. Seropositivity was present in 14.6% of patients and 29% of control subjects and was not statistically significant (p greater than 0.05). The failure to show chlamydial DNA and the lack of serological response to chlamydia make C trachomatis infection a very unlikely factor in the pathogenesis of Crohn's disease.